“GESTIÓN MUNICIPAL DE PROMOCIÓN DE CAPACIDADES EMPRESARIALES EN EL RUBRO CARPINTERíA Y EL DESARROLLO ECONÓMICO LOCAL” DISTRITO DE INDEPENDENCIA - Bustamante Dueñas, Isis (2013)
This research entitled “Municipal Management promotion of entrepreneurial skills in the business carpentry and Local Economic Development”, is developed under the Municipalities Act indicating ... that local governments promote the development of its territorial and activity local business, with criteria of social justice, “... to this concern is investigated how management is given in three fields Municipal being these: Strategic management of local government, developed through the Institutional Operating Plan (IOP) that raises general and specific objectives for the Local Development Management. Operational management, analyzes the role of promoter and facilitator management Local Economic Development in the areas that have a social and economic dynamics emerging in recent years, within which are fourth areas of production and marketing of wood furniture for home and office (the Violets, Mega Furniture, New Millennium, Purina and Other). Finally participative management with those involved in local economic development through management tools to promote entrepreneurial skills (organizing events, fairs, training courses, promotion of partnerships, business promotion programs, etc.. Objects of the present investigation, the study of the promotion of local space and promotion of MSEs, the degree of relationship between the municipal administration to promote entrepreneurial skills by the Local Economic Development Division of the District Municipality of Independencia in item woodwork and local economic development in the district of Independencia. Also identify the meshes or networks of entrepreneurial skills, the degree of development and innovation of these led, led and taught by the municipal administration.